The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Mechanical behaviour, deformation mechanisms and support optimization of tunnels in gentle dip layered rock after freeze–thaw cycles - Xiao-Hu Zhang; Jia-Bing Zhang; Jun-Bin Fu; Rong-Huan Du; Han-Lin Wang (Tunnelling and Underground Space Technology, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

Manure compost and gypsum amendments revitalize soil quality via aggregation and pore structure in the Yellow River Delta - Xiaoyang Duan; Xiaoying Jin; Qi Miao; Zhanlonggang Yu; Hui Rong; Xiao Wang; Zhenling Cui; Hu Zhou; Zhangliu Du (Journal of Soils and Sediments, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Association of phthalate exposure during early pregnancy with fetal growth and the effect modification by gestational stress - Nian Wu; Zhongmei Hu; Xinyi Xiao; Shimin Xiong; Xingyan Liu; Yan Xie; Rong Zeng; Kunming Tian; Xubo Shen; Yuanzhong Zhou; Yijun Liu (International Journal of Hygiene and Environmental Health, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

The mixed-type inhibition of tyrosinase by puerarin: Kinetics and computer simulation - Bo Ma; Rong Li; Feng Li; Xiao Hu; Yechuan Huang (Food Bioscience, 2025)

Single nucleotide variations triggered responsive strip for Helicobacter pylori theranostics - Lin-Min Zhong; Qi-Ling Yang; Xin-Yi Zhong; Xiao-Rong Zhang; Fen-Ying Kong; Shan-Wen Hu; Ai-Lin Liu (Chemical Engineering Journal, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Hydrothermal carbonization: A potent strategy for simultaneously eliminating ARGs-associated pollutants in livestock manure and blocking ARGs horizontal gene transfer - Sunlin Chi; Jinmei Xiao; Jinying Xu; Aijing Li; Jianhui Hu; Xinyi Wang; Meiyan Zhang; Wei Liu; Yalan Zhang; Huijun Ding; Jun Rong; Li Leng; et al. (Journal of Hazardous Materials, 2025)

A new framework integrating crop growth–level IV fugacity model and eco-indicator sensitivity to assess neonicotinoid fate and ecological risk in tropical rice–vegetable rotations - Huadong Tan; Xinyu Hu; Linxia Zhang; Yiru Chen; Rong Hao; Zhenzhen Wang; Chunyuan Wu; Xiaoying Zhang; Xiao Deng; Yi Li; Lin Wu; Yi Zhang (Journal of Hazardous Materials, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

Preparation of high-performance ceramic conductive membranes and applications as the anode and cathode in electrochemical MBRs: antifouling performance and mechanisms - Jinzhuo Shi; Yisong Hu; Songhua Li; Wenqian Xiao; Rong Chen (Journal of Water Process Engineering, 2025)

Analysis of starch structure, functional properties, and the underlying molecular mechanism in SeaRice86 (SR86) - Yongxiang Huang; Xiao Yang; Yilan Cui; Mangu Hu; Yunliang Rong; Yu Ling; Rongchao Yang; Yueqin Zhang (Carbohydrate Polymers, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electro-conductive nylon mesh assisted electro-chemical membrane bioreactor process (EMBR) for municipal wastewater treatment - Songhua Li; Yisong Hu; Jinzhuo Shi; Wenqian Xiao; Yuan Yang; Rong Chen (Journal of Water Process Engineering, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Ferritinophagy-derived iron causes protein nitration and mitochondrial dysfunction in acetaminophen-induced liver injury - Shi-Min Liang; Jie Shen; Rui-Ting Ma; Nan-Di Du; Rui Wang; Zuo-Min Wu; Min Shan; Shi-Rong Liang; Wei-Rong Hu; Wei Wang; Wei-Wei Sheng; De-Feng Huang; et al. (Toxicology and Applied Pharmacology, 2025)

Hydrodynamic perturbations on contaminant behavior in low-permeability sediments: porewater metal dynamics and risk assessment implications - Ning Wang; Hongwei Hu; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Minwei Xie; Stuart L. Simpson (Environmental Pollution, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

High-efficiency immobilization of soil available cadmium by chicken manure and its derivatives: Roles of chemical and microbial property - Zhi-Wen Hu; Feng Jiang; Fei Huang; Heng Wang; Qian-Jun Liu; Xiao Zhou; Ming-Zhi Huang; Peng Wang; Rong-Bo Xiao (Journal of Environmental Chemical Engineering, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Spectral and color temperature dependence of LED exposure on retinal damage and the protective effects of neohesperidin - Rong Lin; Kunhong Xiao; Boyuan Wen; Huazhi Ma; Yuting Hu; Yan Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Optimization strategy for Cr(VI) removal in coke-based modular constructed wetlands: A comprehensive analysis of purification efficiency, removal mechanisms, and practical feasibility - Xinlu Xiao; Xuhao Li; Xiangling Zhang; Chen Wang; Xiaoting Liu; Jing Bai; Rong Zhang; Shilong Cao; Jiezhou Hu; Zhenchao Liu; Jun Shen (Journal of Environmental Management, 2025)

Struvite precipitation for low-level ammonium removal in mariculture wastewater: Feasibility study - Jia Hui Ong; Shuntian Huang; Xiao Hu; Rong Xu (Bioresource Technology, 2025)

Paleoproterozoic orogenic event in the western North China Craton: Insights from zircon U-Pb-Lu-Hf isotopes and geochemistry of meta-supracrustal rocks in the Beidashan complex, Alxa block - Yi-Wei Rong; Wen-Bin Zhu; Xi Wang; Jun-Yue Zhu; Xiao Hu (Precambrian Research, 2025)

Operational characteristics and phosphorus recycling potential of a hydroxyapatite (HAP)-anammox process at high nitrogen loading rate - Wenqian Xiao; Yisong Hu; Songhua Li; Jinzhuo Shi; Wenrui Tian; Yi Xue; Rong Chen (Journal of Environmental Chemical Engineering, 2025)

The diverse sleep structure of mid-day nap in college students - Qin Xiao; Xueqi Sun; Guoxin Zeng; Xin Luo; Qian Jiang; Rong Ren; Xiangdong Tang; Chao He; Zhian Hu; Fenlan Luo; Jie Yan (Sleep and Biological Rhythms, 2025)

1DCNN-based prediction methods for subsequent settlement of subgrade with limited monitoring data - Sen-Lin Xie; Anfeng Hu; Meihui Wang; Zhi-Rong Xiao; Tang Li; Chi Wang (European Journal of Environmental and Civil Engineering, 2025)

Inhibition regulatory mechanism in Staphylococcus aureus under cold plasma oxidative stress - Rong Du; Xiao Yang; Jun-Hu Cheng (Food Bioscience, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Airborne Investigation of Riming: Cloud and Precipitation Microphysics within a Weak Convective System in North China - Xiangfeng Hu; Hao Huang; Shaoyu Hou; Kun Zhao; Chuanfeng Zhao; Yinghui Lu; Jiefang Yang; Rong Zhang; Delong Zhao; Weiguo Liu; Dan Zhang; Haixia Xiao (Advances in Atmospheric Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic insights into efficient phosphorus adsorption and recovery from water using functional ZnO/ZnFe-LDHs alginate hydrogels - Shilong Cao; Xiangling Zhang; Shuqin Xie; Chen Wang; Jing Bai; Xuhao Li; Rong Zhang; Xinlu Xiao; Jiezhou Hu; Xiaoxia Jiang (Journal of Environmental Chemical Engineering, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

Nickel-iron layered double hydroxide and CoMoO4 composites supported on nickel foam as efficient bifunctional catalyst for water electrolysis - Xin Xiao; Rao Ma; Ke Jiang; Lushan Ma; Qiyao Wang; Shuang Meng; Tong Yang; Zhuo Qiu; Rong Hu; Long Huang (Fuel, 2025)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Catalytically ultrathin titania coating to enhance energy storage and release of aluminum hydride via atomic layer deposition - Zhijia Hu; Xingxing Xu; Huachen Shao; Ruidong Luo; Mingxuan Wang; Gen Tang; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

Chemical constituents from Croton lauioides Radcl.-Sm. & Govaerts and their chemotaxonomic significance - Jia-Xin Hu; Qian Liang; Li-Lin Xiao; Rong-Lin Jia; Xiao-Min Su; Wen-Hui Xu (Biochemical Systematics and Ecology, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Photo-enhanced nanozyme with self-cascade catalysis enhances peroxidase-like activity for alcohol discrimination - Rina Su; Yu Wu; Weiqing Xu; Rong Tan; Ying Qin; Runshi Xiao; Canglong Wang; Liuyong Hu; Wenling Gu; Hongcheng Sun; Chengzhou Zhu (Chemical Engineering Journal, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

Blockade of the Dopamine D3 Receptor Attenuates Opioids-Induced Addictive Behaviours Associated with Inhibiting the Mesolimbic Dopamine System - Rong-Rong Hu; Meng-Die Yang; Xiao-Yan Ding; Ning Wu; Jin Li; Rui Song (Neuroscience Bulletin, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Tigliane diterpenoids with cytotoxic activities from Croton damayeshu - Rong-Lin Jia; Qian Liang; Jia-Xin Hu; Si-Da Xie; Xiao-Min Su; Wen-Hui Xu (Phytochemistry Letters, 2023)

Direct discharge of sewage to natural water through illicitly connected urban stormwater systems: An overlooked source of dissolved organic matter - Ruihua Zhang; Rong Xiao; Feifei Wang; Wenhai Chu; Jinglong Hu; Yu Zhang; Wei Jin; Jan Peter van der Hoek; Zuxin Xu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Prediction of daily PM2.5 and ozone based on high-density weather stations in China: Nonlinear effects of meteorology, human and ecosystem health risks - Lili Wang; Boya Liu; Rong Li; Xingfeng Chen; Lili Liu; Xiao Tang; Jingda Liu; Zhiheng Liao; Jinyuan Xin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Lithologic control of soil C:N:P stoichiometry across a climatic gradient in southwest China - Mingming Sun; Rong Yang; Yixin Tang; Dan Xiao; Wei Zhang; Zhihong Xu; Zhihua Shi; Peilei Hu; Hanqing Wu; Kelin Wang (Journal of Soils and Sediments, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Testing of Mode-I Fracture Toughness of Sandstone Based on the Fracturing Mechanism of an Explosion Stress Wave - Dingjun Xiao; Wentao Yang; Chuanju Liu; Rong Hu (Rock Mechanics and Rock Engineering, 2022)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Occurrence and damage of epidemic fungal diseases in middle and late stages of sugarcane growth in Yunnan Province of China - Wen-Feng Li; Xiao-Yan Wang; Hong-Li Shan; Rong-Yue Zhang; Yin-Hu Li; Wen-Jie Lu; Ying-Kun Huang (European Journal of Plant Pathology, 2022)

A study on the enrichment mechanism of three nitrophenol isomers in environmental water samples by charge transfer supramolecular-mediated hollow fiber liquid-phase microextraction - Zhao-hui Wang; Dou-dou Xu; Xiao-hong Bai; Shuang Hu; Rong-rong Xing; Xuan Chen (Environmental Science and Pollution Research, 2022)

Metabolomics analysis of the potential toxicological mechanisms of diquat dibromide herbicide in adult zebrafish (Danio rerio) liver - Ye Xiao; Xiang Lin; Meilan Zhou; Tianyu Ren; Ruili Gao; Zhongqun Liu; Wenjing Shen; Rong Wang; Xi Xie; Yanting Song; Wenting Hu (Fish Physiology and Biochemistry, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

A novel alkaloid from the seeds of Sophora alopecuroides L - Zi-Jian Rong; Xiao-Xu Gao; Gao-Sheng Hu; Ting Yan; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2022)

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Reduction of mussel metamorphosis by inactivation of the bacterial thioesterase gene via alteration of the fatty acid composition - Xiao-Meng Hu; Junbo Zhang; Wen-Yang Ding; Xiao Liang; Rong Wan; Sergey Dobretsov; Jin-Long Yang (Biofouling, 2021)

Genotypic variation in nitrogen utilization efficiency in oilseed rape is related to the coordination of leaf senescence and root N uptake during reproductive stage - Huiying He; Yuyu Xie; Anyu Zhao; Wencong Hu; Xiao Guo; Anthony J. Miller; Xiaoming Wu; Biyun Chen; Rong Zhang; Hui Tian; Yajun Gao (Plant and Soil, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Disruption of functional connectivity among subcortical arousal system and cortical networks in temporal lobe epilepsy - Rong Li; Chongyu Hu; Liangcheng Wang; Ding Liu; Dingyang Liu; Wei Liao; Bo Xiao; Huafu Chen; Li Feng (Brain Imaging and Behavior, 2020)

Transdermal Administration of Ibuprofen-Loaded Gel: Preparation, Pharmacokinetic Profile, and Tissue Distribution - Meng-qiu Xia; Chun-ling Tian; Liu Liu; Rong-feng Hu; Shuang-ying Gui; Xiao-qin Chu (AAPS PharmSciTech, 2020)

lncRNA H19 sponging miR-93 to regulate inflammation in retinal epithelial cells under hyperglycemia via XBP1s - Rong Luo; Fan Xiao; Pei Wang; Yu-Xiang Hu (Inflammation Research, 2020)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Molecular and morphological data reveals new insights into genetic diversity and population structure of Chinese cherry (Prunus pseudocerasus Lindl.) landraces - Tao Chen; Yue-yang Hu; Qing Chen; Yan Wang; Jing Zhang; Hao-ru Tang; Xiao-rong Wang (Genetic Resources and Crop Evolution, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Immunosuppressive Effect of Hypodermin C on Complement Component 3 In Vitro - An-Kang Hu; Ren-Jin Chen; Xiao-Rong Zhu; Jian-Hong Gu; Zong-Ping Liu (Cell Biochemistry and Biophysics, 2015)

Bacterial composition and spatiotemporal variation in sediments of Jiaozhou Bay, China - Xin Liu; Hang-Wei Hu; Yu-Rong Liu; Ke-Qing Xiao; Fan-Sheng Cheng; Ji Li; Tian Xiao (Journal of Soils and Sediments, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Effects of Estradiol on Voltage-Gated Potassium Channels in Mouse Dorsal Root Ganglion Neurons - Juan Du; Qiang Wang; Fang Hu; Jun Wang; Haixia Ding; Rong Gao; Hang Xiao; Lin Wang (The Journal of Membrane Biology, 2014)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

Soil nitrification and foliar δ15N declined with stand age in trembling aspen and jack pine forests in northern Alberta, Canada - Ya-Lin Hu; En-Rong Yan; Woo-Jung Choi; Francis Salifu; Xiao Tan; Z. Chi Chen; De-Hui Zeng; Scott X. Chang (Plant and Soil, 2014)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Interleukin-23 as a potential therapeutic target for rheumatoid arthritis - Chao Rong; Wei Hu; Fan-rong Wu; Xiao-juan Cao; Fei-hu Chen (Molecular and Cellular Biochemistry, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Genomic rearrangement between wheat and Thinopyrum elongatum revealed by mapped functional molecular markers - Li-Jun Hu; Cheng Liu; Zi-Xian Zeng; Guang-Rong Li; Xiao-Jin Song; Zu-Jun Yang (Genes & Genomics, 2012)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Complete genome sequence of a tomato spotted wilt virus isolate from China and comparison to other TSWV isolates of different geographic origin - Zhong-Ze Hu; Zhi-Ke Feng; Zhi-Jun Zhang; Yao-Bin Liu; Xiao-Rong Tao (Archives of Virology, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Relaxation Effects of a Saturated Porous Media Using the Two-Dimensional Generalized Thermoelastic Theory - Gan-bin Liu; Shi-rong Ding; Rong-hua Ye; Xiao-hu Liu (Transport in Porous Media, 2011)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

The complete mitogenome and phylogenetic analysis of Bombyx mandarina strain Qingzhou - Xiao-long Hu; Guang-li Cao; Ren-yu Xue; Xiao-jian Zheng; Xing Zhang; Hai-rong Duan; Cheng-liang Gong (Molecular Biology Reports, 2010)

Mechanism of the Formation for Thoracic Impedance Change - Ming-Xing Kuang; Qiu-Jin Xiao; Chao-Ying Cui; Nan-Zhen Kuang; Wen-Qin Hong; Ai-Rong Hu (Annals of Biomedical Engineering, 2010)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Inheritance of the Triple-spikelet Character in a Tibetan Landrace of Common Wheat - Wu-Yun Yang; Bao-Rong Lu; Xiao-Rong Hu; Yi Yu; Yong Zhang (Genetic Resources and Crop Evolution, 2005)

Inheritance in hexaploid wheat of genes for hairy auricles and hairy leaf sheath derived from Aegilops tauschii Coss. - Yang Wu-Yun; Wu Bei-Hua; Hu Xiao-Rong; Ye Yi; Zhang Yong (Genetic Resources and Crop Evolution, 1999)